2010
DOI: 10.2109/jcersj2.118.758
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and fluorescence properties of novel alkaline earth silicate phosphors by reduction treatment of Eu3+ to Eu2+

Abstract: The synthesis and emission spectrum control of novel Eu 2+ -activated amorphous alkaline earth silicate phosphors from the reduction of Eu 3+ -activated amorphous alkaline earth silicate phosphors is reported. The as-prepared Eu 3+ -activated amorphous alkaline earth silicate phosphors emitted red. Reduction using Ni-metal powder in a H 2 (5%)/Ar (95%) atmosphere produced Eu 2+ -activated amorphous barium silicate phosphor that emitted green. Eu 2+ -activated amorphous calcium silicate was produced by reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The relative emission intensities for each phosphor increased with an increase in the initial Eu/(Eu +M) atomic ratio. These linearly proportional results are similar to those observed for the CSH phosphor [6,9]. The Ba type did not exhibit concentration quenching until the initial Eu/(Eu+Ba) atomic ratio reached 0.25.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The relative emission intensities for each phosphor increased with an increase in the initial Eu/(Eu +M) atomic ratio. These linearly proportional results are similar to those observed for the CSH phosphor [6,9]. The Ba type did not exhibit concentration quenching until the initial Eu/(Eu+Ba) atomic ratio reached 0.25.…”
Section: Resultssupporting
confidence: 87%
“…3. Because calcium silicate hydrate decomposes at 854 1C [9], the Eu 3 + -activated alkaline earth silicate hydrate phosphors containing Sr and Ba were heated at 850 1C. At each initial Eu/(Eu+M) atomic ratio, the amorphous state was observed following heat treatment at 850 1C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the authors reported on synthesis and fluorescence properties of the phosphors which was reduced Eu 3+ -activated amorphous calcium silicate phosphor and was used alkaline-earth metal ions substitution for Ca 2+ ion [6,7]. We tried the synthesis of amorphous calcium silicate phosphor which was green emitting by using Tb 3+ ion in substitution for Eu 3+ ion in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…We have performed a series of studies on the synthesis of phosphors by liquid-phase reactions [1][2][3][4][5][6][7][8][9][10]. In these liquid-phase reactions, an activator can be incorporated into the phosphor structure with uniform distribution.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, precursor phosphors formed by liquid-phase reaction can also be subjected to calcination. Calcium silicate hydrate (CSH), another phosphor precursor, has a layered structure and can be synthesized easily by liquid-phase reaction under ambient pressure at near room temperature [8][9][10]. When doping activators were included in the interlayers of a CSH phosphor, concentration quenching did not occur until much higher concentrations than typically observed.…”
Section: Introductionmentioning
confidence: 99%